2017
DOI: 10.1021/acs.biomac.6b01723
|View full text |Cite
|
Sign up to set email alerts
|

Design of Stomach Acid-Stable and Mucin-Binding Enzyme Polymer Conjugates

Abstract: The reduced immunogenicity and increased stability of protein-polymer conjugates has made their use in therapeutic applications particularly attractive. However, the physicochemical interactions between polymer and protein, as well as the effect of this interaction on protein activity and stability, are still not fully understood. In this work, polymer-based protein engineering was used to examine the role of polymer physicochemical properties on the activity and stability of the chymotrypsin-polymer conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 66 publications
3
51
0
Order By: Relevance
“…Non-covalent polymer-protein binding studies, sometimes involvingd elivery experiments, is ab road field, and additional reports relatedt ot his topic that highlight various binding interactions and characterization methods can be found in Refs. [58][59][60][61][62][63][64][65][66][67][68][69][70][71].B inding studies showcasing availablet echniques could potentially contain criticali nformation necessary for future protein-delivery optimization studies and should not be overlooked.…”
Section: Other Non-covalent Protein-basedcomplexes For Deliverymentioning
confidence: 99%
“…Non-covalent polymer-protein binding studies, sometimes involvingd elivery experiments, is ab road field, and additional reports relatedt ot his topic that highlight various binding interactions and characterization methods can be found in Refs. [58][59][60][61][62][63][64][65][66][67][68][69][70][71].B inding studies showcasing availablet echniques could potentially contain criticali nformation necessary for future protein-delivery optimization studies and should not be overlooked.…”
Section: Other Non-covalent Protein-basedcomplexes For Deliverymentioning
confidence: 99%
“…It is hypothesized that the bridging of disulfide bonds with a maleimide moiety could introduce additional stability, through preventing disulfide reduction. The study reported here investigated the formation of functionalized MAMs, ABMs and DTMs in enzyme conjugations and how the substituents affect the integrity of two enzymes, α‐chymotrypsin (α‐CT) and human lysozyme (HLZ), which are enzymes commonly used in conjugation‐based applications and have been extensively characterized …”
Section: Introductionmentioning
confidence: 99%
“…Since the first studies of protein‐ATRP, protein–polymer conjugates with different polymer architectures and functionalities have been synthesized to manipulate the activity, stability, and substrate binding affinity of the conjugate. These previous studies indicated that to provide consistent and reliable performance, conjugates must be homogeneous in the number of chains attached and have low molar mass dispersities.…”
Section: Introductionmentioning
confidence: 99%